Fostering Economic Empowerment and Child Protection in Sungai Penuh City: The Role of Dharma Wanita Association's Socialization and Entrepreneurship Training - Efdison, Zefri; Lova, Anggil; Yelnim, Yelnim; Sudirman, Sudirman; Pramurza, Dede (Research Horizon, 2023)
Entrepreneurship training is a crucial step in the process of developing quality human resources. This community service is conducted with the primary objective of empowering women in Sungai Penuh City by enhancing their entrepreneurial knowledge, leading to increased family income and economic stability. The entrepreneurship socialization and training program witnessed participation from 103 attendees, mainly students affiliated with the Dharma Wanita of Sungai Penuh City who displayed a keen interest in entrepreneurship. The training sessions focused on delivering comprehensive education and guidance in both traditional and digital marketing aspects of entrepreneurship. The outcome of this initiative is reflected in the training's results, which indicated that among the 103 participants, only three individuals faced persistent challenges in comprehension. Consequently, it can be inferred that the goals of this endeavor have been successfully attained.